Eco-Linguistics in Action: Themes and Trends in Environmental Projects - Rabbianty, Eva Nikmatul; Ariwidodo, Eko; Syafik, Moh.; Widiati, Utami (Universitas Islam Negeri Madura, 2025)
Environmental project-based language learning (EPBLL) is a promising approach for promoting language acquisition, environmental consciousness, and sustainable education among young learners. However, the present state of research on EPBLL in English language education for early learners needs to be better understood. This bibliometric study examines the state of EPBLL research over the past ten years. We conducted a bibliometric analysis of articles published between 2013 and 2023 that met our inclusion criteria using Scopus. Our analysis focused on publication trends, journal sources, citation counts, and identifying major research topics and themes in EPBLL research. Our study found a steady increase in EPBLL publications over the past ten years, with numerous journals contributing to this research field. We identified several important themes and areas of emphasis, such as the role of technology in EPBLL, the impact of EPBLL on language acquisition and environmental awareness, and the effectiveness of various pedagogical approaches to EPBLL. Our findings have significant implications for educators, researchers, and policymakers promoting sustainable education and language acquisition through project-based learning. This study provides insights into the state of EPBLL research in English language education for young learners and highlights essential research themes that can inform future studies in this area.